2013
DOI: 10.3389/fpls.2013.00050
|View full text |Cite
|
Sign up to set email alerts
|

Grass cell wall feruloylation: distribution of bound ferulate and candidate gene expression in Brachypodium distachyon

Abstract: The cell walls of grasses such as wheat, maize, rice, and sugar cane, contain large amounts of ferulate that is ester-linked to the cell wall polysaccharide glucuronoarabinoxylan (GAX). This ferulate is considered to limit the digestibility of polysaccharide in grass biomass as it forms covalent linkages between polysaccharide and lignin components. Candidate genes within a grass-specific clade of the BAHD acyl-coA transferase superfamily have been identified as being responsible for the ester linkage of ferul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 37 publications
(54 reference statements)
2
70
1
Order By: Relevance
“…The predicted protein Bradi2g36910 was found to have the highest sequence homology to OsPMT, sharing 63% amino acid sequence identity and 75% similarity. Recently published phylogenetic trees that contained both Brachypodium and rice BAHD acyltransferases showed that Bradi2g36910 is the most closely related Brachypodium protein to OsPMT (Bartley et al , 2013; Molinari et al , 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The predicted protein Bradi2g36910 was found to have the highest sequence homology to OsPMT, sharing 63% amino acid sequence identity and 75% similarity. Recently published phylogenetic trees that contained both Brachypodium and rice BAHD acyltransferases showed that Bradi2g36910 is the most closely related Brachypodium protein to OsPMT (Bartley et al , 2013; Molinari et al , 2013). …”
Section: Resultsmentioning
confidence: 99%
“…A study of gene deregulation in rice supported the involvement of these putative feruloyl-transferases [103]. Investigations in Brachypodium [96] suggested that the most probable candidates for arabinoxylan feruloylation were the orthologs of BAHD genes in the OsAt1/2/6/7/8/9-like sub-clade. Out of the seven maize orthologs of the rice BAHD genes, only two colocalizations were observed with IVNDFD QTLs, in bins 3.09 and 6.05.…”
Section: Arabinoxylan Feruloylation and Ferulate Cross-linkagesmentioning
confidence: 94%
“…Several members of the GT61 family (clade A) were shown to be xylan O-3-arabinosyltransferases in wheat and rice [90,95,96]. A mutation in a GT61 gene, involved in arabinoxylan substitution, was shown to improve saccharification in Brachypodium plants, without any significant alteration in plant growth or stem strength [97].…”
Section: Synthesis and Arabinosylation Of Glucuronoxylan Chainsmentioning
confidence: 98%
“…Gymnosperms contain almost entirely G unit in lignins; dicotyledonous angiosperms contain G and S units in lignins; and all the G, S, and H units can be found in monocotyledonous lignins [5]. Other units with relatively fewer contents were also identified in the lignin of LCBM, such as ferulates and coumarates [6]. Biosynthesis of lignin is a process that monomers undergo radical coupling reactions to form racemic, cross-linked, and phenolic polymer, by which lignin content and composition may vary significantly in different LCBMs [7].…”
Section: Introductionmentioning
confidence: 92%